EKSPLORASI KONSORSIUM MIKROB FILOSFER DAN RIZOSFER ASAL BERBAGAI EKOSISTEM DI KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Aris Aksarah Pas; Didy Sopandie; Trikoesoemaningtyas Trikoesoemaningtyas; Dwi Andreas Santosa (Jurnal Agrotech, 2018)
Microbial consortium exploration in an ecosystem is a series of activities aimed at obtaining microb living in a consortium and beneficial to plant growth.The study aimed to obtain leaf and soil samples in various plants within an ecosystem, as a source of a consortium of microbial phyllosphere and rhizosphere to be tested for their effectiveness in increasing the growth and yield of rice crops. The method of determining the location is based on the method of transect sampling/line intersep plot design on an area of 5,196.02 km2. Site determination based on purposive sampling includes ecosystems: rice fields, gardens, pastures and forests.The results showed that, Sigi District has biodiversity in various ecosystems that have potential as source of consortium of microbial phyllosphere and rhizosphere. From the exploration results obtained a sample of 48 species of plants consisting of plants under the level of 30 species, 12 pile poles and 6 types of stakes. The results of the isolation of leaf and soil samples obtained 144 consortium of microbial phyllosphere and 48 consortium of microbial rhizosphere. The obtained consortium was then tested for its effectiveness on the growth and yield of rice crops in the next stage of the study